ISOLATION AND CHARACTERIZATION OF FLAVONE GLYCOSIDE VITEXIN FROM PEPEROMIA PELLUCIDA LINN - pappachen, leena k (Journal of Drug Delivery and Therapeutics, 2013)
Peperomia Pellucida Linn , widely used in  traditional medicine belongs to the family Piperaceae. It  has been used for treating abdominal pain, acne ,boils, colic, fatigue, gout, headache, renal disorders, and rheumatic joint pain. The whole plant after collection, authentication and drying, was extracted with petroleum ether, chloroform, methanol and water using soxhlet extractor. The aim of the  study  was to isolate the phytoconstituents  from the  methanolic extract of peperomia pellucida by Preparative-Thin Layer Chromatography (P-TLC) and characterized by spectroscopic techniques (UV-visible spectroscopy, infrared spectroscopy,1H and 13C NMR spectroscopy and mass spectrometry). A flavonoidal structure was isolated from the methanolic extract of the plant. The light yellow coloured compound which solubilizes in methanol, ethanol and water having m.p. 203-204Oc and Rf value 0.61 in mobile phase acetonitrile : water: acetic acid (6:4:0.1) was identified by the various spectroscopical methods. So from this study, it is concluded that the isolated compound may be vitexin which is responsible for various pharmacological activities of the plants.